EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE STRUCTURED NUMBERED HEADS (SNH) DAN NUMBERED HEADS TOGETHER (NHT) DENGAN PENDEKATAN MATEMATIKA REALISTIK PADA PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KEMANDIRIAN BELAJAR SISWA - Jannah, Raodatul; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2013)
models of SNH type, NHT type with realistic Mathematics approach, and conventional type results in a better learning achievement in Mathematics of the students; (2) which of the high, the medium, and the low independence of learning of the students results in a better learning achievement in Mathematics; (3) for each category of independence of learning of the students, which one results in better achievement in Mathematics, cooperative learning model of SNH type, NHT type with realistic Mathematics approach, and conventional type; and (4) for each learning model, which one results in better achievement in Mathematics, students who have high, middle, or low independence of learning. This research used quasi-experimental research method. The population of this research was the eleventh (8th) grade students of the state junior high schools in Mataram in the first semester of the academic year of 2012/2013. This research used stratified cluster random sampling technique. The sample of this research consisted of the students of SMP Negeri 15 Mataram, SMP Negeri 8 Mataram, SMP Negeri 9 Mataram. The data of the research were collected through documentation, questionnaire, and test. The data were then analyzed by using the unbalanced Two-Way Analysis of Variance at the significance level of 0.05. The results of the research are as follows: (1) the SNH type results in a better learning achievement in Mathematics of the students than cooperative learning model of NHT type and conventional type, and the cooperative learning model of NHT type results in a better learning achievement in Mathematics of the students than conventional type; (2) the learning achievement of the students with the high independence of learning results in a better achievement than the learning achievement of the students with the middle and low independence of learning and the learning achievement of the students with the middle independence of learning give the same mathematics achievement as the low independence of learning; (3) for each category of independence of learning of the students, cooperative learning model of SNH type results in better achievement in Mathematics than cooperative model NHT type and conventional type, and cooperative learning model NHT type results in a better learning achievement in Mathematics of the students than conventional type; and (4) for each learning model, the learning achievement of the students with the high independence of learning results in a better achievement than the learning achievement of the students with the middle and low independence of learning and the learning achievement of the students with the middle independence of learning results as good as in the low independence of learning.Keywords: Cooperative learning model of SNH type, NHT type, realistic Mathematics approach, and independence of learning of the students